Eating and Grooming Abilities Predict Outcomes in Patients with Early Middle Cerebral Infarction: A Retrospective Cohort Study - Yumi Suzuki; Sachiko Tsubakino; Hiromi Fujii (Hindawi-Wiley, 2020)
Patients with cerebrovascular disorders are often forced to rest, with early prognosis made by bedside examination. However, overloading, for example, talking for a long time, may worsen the condition. We hypothesized that activities of daily living (ADL) from the Functional Independence Measure (FIM) that were actually performed regularly are useful to predict prognosis. The present study was aimed at determining the predictive items related to predicting prognosis from the status of early motor paralysis and ADL in patients with acute middle cerebral artery (MCA) infarction. We examined 367 patients with MCA infarction for Brunnstrom recovery stage (BRS) and FIM within 4 days of admission and modified the Rankin Scale before onset and just before discharge. Logistic regression analysis was used to compare two groups of patients based on their postdischarge destination (Home/another hospital or facility). The logistic regression analysis showed the following: BRS Hand: odds ratio (OR) 1.641 (95% CI 1.642 (1.336-2.017), p<0.001); FIM Grooming: OR 1.279 (95% CI 1.220-1.807, p<0.001); and FIM Eating: OR 1.280 (95% CI 1.102-1.488, p<0.001). On the other hand, the ROC analysis showed the ROC area for Eating to be 0.830 (95% CI 0.787-0.874), for Grooming to be 0.81 (95% CI 0.765-0.865), and for BRS Hand to be 0.805 (95% CI 0.760-0.851). The BRS Hand and FIM Eating and Grooming domains were identified as predictive factors using the following cutoff points: BRS Hand stage V and FIM scores of 5 for Eating and 4 for Grooming. The cutoff points for the BRS Hand and FIM Eating revealed that, at a minimum, such patients can use the nonaffected hand. The presence of cognitive dysfunction or dysphagia affects these domains. Therefore, these results suggested that Eating and Grooming are appropriate as evaluation items.